Site-specific deterministic seismic hazard analysis of Surabaya, Indonesia - Deng, Xiaofang (2015)
The seismic hazard assessment has been performed extensively in the past decades. Most of the studies focus on the zone with medium to high seismicity. However, recently studies have found that the zone with low seismicity also has a high potential of seismic hazards, especially for the zone with soft sedimentary deposit due to the amplification influence in the local site. As Surabaya, Indonesia has a potential severe seismic hazard due to its special geotechnical conditions and locations, it was selected as a case study in this investigation. It should also be noted that before this work, limited studies have been conducted in this region regarding seismic hazard assessment. For this purpose, a series of measurements and analyses were carried out in Surabaya. Firstly, the shear-wave velocity structures in the study area were investigated using the microtremor-array measurements. It was found that deep soft sediments (375 to 750 m) are overlaid underneath Surabaya. The site class of the study area is defined as site class D in the southwest area and site class E in the northeast area. Secondly, the potential earthquake scenarios affecting the study area were determined by considering the seismicity, geological and historical earthquake data. It was concluded that the Mw8.2 subduction earthquake and the Mw6.7 Kendeng earthquake are the two most critical earthquake scenarios affecting Surabaya. Thirdly, the ground motions at the bedrock from two controlling earthquake scenarios were simulated by the hybrid kinematic-stochastic method. Finally, the ground motions at the surface were generated from site response study using the program DEEPSOIL. It was found that the existing Indonesia National Standard 1726-2002 (SNI-1726-2002) would lead to an unsafe design of buildings with long period in site class D and with short period in site class E. It is hoped that the findings from this research study can help improve the existing design code SNI-1726-2002 and provide systematic procedures for studying the local site effects in other similar zone with low seismicity.